Knowledge, attitude, and practice of coral reef conservation among Terengganu community of Malaysia - Marzo, Roy Rillera; Chen, Hana W. Jun; Anuar, Haryati; Abdul Wahab, Mohamad Khairuddin; Nizam, Mohamad Hairul; Ariffin, Indang Ariati; Hamzah, Hazian; Ahmad, Azral Ismawy; Kawuki, Joseph; Halim, Shariff; Aljuaid, Mohammed (Frontiers in Environmental Science, 2023)
Background: Malaysia's coral reefs, primarily threatened by overfishing, pollution, and climate change, face significant challenges despite conservation efforts. Researchers from Management and Science University have taken a holistic approach towards coral reef conservation. This multi-stakeholder strategy, which involves local communities, government agencies, and private sectors, underscores the importance of collective action. A notable initiative within this approach is the coral transplantation program on Geluk Island, aiming to restore and bolster these crucial marine ecosystems.Objective: This study aimed to investigate the knowledge, attitudes, and practices of the Terengganu community towards coral reef conservation and identify sociodemographic variables associated with community member practices.Methodology: This was a cross-sectional study conducted from July to October 2022 in Setiu, Terengganu and recruited 338 adult local villagers. Data on participants' sociodemographic characteristics, knowledge of coral reefs, awareness and attitude towards the MYCoral 5.0 MSU Eco-Marine Project, and practice of coral reef conservation were collected via validated interviewer-rated questionnaires. Logistic regression analysis was conducted to identify factors associated with good coral reef conservation practices, using SPSS version 2.Results: Out of the 338 participants, 55.3% had acceptable knowledge on coral reefs, 29.0% had good practice of coral reef conservation. Additionally, 44.7% had good knowledge of the MyCoral 5.0 project, and 68.9% were willing to volunteer for coral reef conservation. Knowledge of coral reefs (AOR=1.22, 95%CI: 1.15-2.52), knowledge of MyCoral project (AOR=2.64, 95%CI: 1.47-4.74), and willingness to volunteer for conservation (AOR=1.66, 95%CI: 1.36-3.64) were significantly associated with good practice of coral reef conservation.The study results highlight a need for education and awareness programs to improve the knowledge and practices of coral reef conservation. Moreover, consideration of socio-demographic dynamics of the local communities in designing targeted conservation strategies could also be vital.